Sistema de inovação do setor de celulose e papel brasileiro : o caso da Aracruz Celulose e o projeto Genolyptus - Campos, Sérgio Antonio Ribeiro (2010)
This thesis assesses asa project of cooperation for the production of knowledge (the Genolyptus project) represents a linkage among the innovation system elements of the pulp and paper sector in Brazil. It search understand the project from a member’s perspective (the Aracruz Celulose) analyzing how the company operates in the sectoral system and measuring the impact generated by its insertion in the SSI onits evolution. To do this it established an understanding on the key determinants of innovationin the Freeman-Aalborg tradition of the systems innovationapproach. This tradition is based on three basic pillars: knowledge, learning processes and interactions between different actors of the SI. Its main focus of analysis refers to the spatial ambit more specifically to national level with interest in the comparison of strategies for economic policy and economic standards among several countries. However, other levels of analysis derived from this tradition as in the casehere examined. The SI's approach here used is that dedicated specifically to the sectoral level whose the interest is in understanding how technologies and products develops in specific sectors, which are its basic elements and what influence of each factor in technologies and products evolution. This thesis highlight that articulation of SIS's elements had great impact on innovations development in building of Genolyptus Project as well as in Aracruz Celulose evolution. Moreover stresses the important role played by the State, the importance of accumulated knowledge base, learning processes, relations and interactions among different agents in the system to the innovations development.